Optimale internationale Arbeitsteilung - Thieß Petersen (Wirtschaftsdienst, 2020)
Die internationale Arbeitsteilung bietet für eine Volkswirtschaft sowohl Vorals auch Nachteile. Sofern die damit verbundenen Grenzkosten und Grenznutzen die üblichen Verläufe aufweisen, gibt es für jedes Land ein optimales Ausmaß dieser Arbeitsteilung. Die Corona-Pandemie dürfte die Grundlagen für die entsprechenden Entscheidungen im Bereich der internationalen Arbeitsteilung–sowohl aus Sicht der Unternehmen als auch aus Sicht der gesamten Gesellschaft–deutlich verändern. – – The international division of labour implies both advantages and disadvantages to an economy. As long as the marginal costs and marginal benefi ts associated with the international division of labour stick to standard economic theory, there is an optimal degree of this division for every economy. The corona pandemic is likely to change the fundamentals for relevant decisions–both from the perspective of companies and of the society as a whole–in such a way that the extent of the division of labour and international trade will decrease correspondingly.
Keywords: F10; F50; F60; 330